Circ_0008450 downregulates Runx3 to promote the proliferation and epithelial-mesenchymal transition of human keratinized epithelial cells. Issue 23 (1st December 2020) - Chen, Huaxia; Xu, Xiao; Lai, Linying; Huo, Ran; Chen, Minliang
ABSTRACT: Keloid is an extremely common and often overlooked benign neoplastic disease, but its consequences should not be underestimated. Therefore, a deep exploration of the pathological mechanism of keloid becomes very essential. After 22 samples were collected from each patient's keloid tissues and normal skin tissues, circ_0008450 and Runx3 expression was tested by qRT-PCR. When primary human keratinized epithelial cells were transfected by sh-circ_0008450 or sh-Runx3, cell proliferation, apoptosis, migration, and EMT process were assessed by CCK-8, BrdU assay, apoptosis assay, migration assay, and Western blot. Finally, transfection was performed to explore the effect of circ_0008450 on the TGF-β/Smad signal pathway by adopting western blot. Circ_0008450 was highly expressed in keratinized epithelial tissues. After the transfection of sh-circ_0008450 into primary human keratinized epithelial cells, cell proliferation, migration, and EMT process were inhibited, and apoptosis was stimulated. Moreover, circ_0008450 silence-induced above changes were partly reversed by transfecting sh-Runx3. In addition, transfecting sh-circ_0008450 could repress TGF-β/Smad pathway, while transfecting sh-Runx3 activated the above pathway. Circ_0008450 down-regulated Runx3 to promote the proliferation and EMT process of human keratinized epithelial cells. This discovery may be related to the activation of the TGF-β/Smad pathway.